St. Vincent and the Grenadines : Recent Economic Development. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1997)
This paper describes economic developments in St. Vincent and the Grenadines during the 1990s. Between 1990 and 1995, real GDP growth (at factor costs) averaged 4 percent per year, but varied widely from year to year, largely reflecting developments in the banana industry, St. Vincent's principal crop. After three years of solid growth in 1990-92, the economy stagnated in 1993-94, as severe weather conditions sharply reduced banana harvests. Real GDP growth climbed to more than 7 percent in 1995 with a substantial recovery in banana production.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet